A micro and macro prudential approach to financial soundness assessment of Commercial Banks in Kenya - Kolum, Micah Cheruiyot (Strathmore University, 2016)
Financial soundness of the banking system is underpinned through effective bank assessment and monitoring. The prevalence of bank failures in Kenya raises the question on how best to identify vulnerabilities in financial condition of banks. This thesis aimed to identify the set of CAMELS-based financial soundness indicators that discriminate between sound and unsound banks, determine whether selected macro-economic indicators have an impact on bank financial soundness and to assess the performance of CAMEL as a tool for assessing bank soundness. The thesis adopted explanatory and descriptive research designs. Secondary data on financial soundness indicators were obtained from bank balance sheets and income statements and those on macro-economic environment obtained from the CBK website. Data analysis and presentation was done using descriptive statistics, binary logistic regression, CAMEL, CAMELS and Z-score index models. The results suggest that the statistically significant indicators discriminating between sound and unsound banks are capital adequacy, asset quality, management quality and liquidity. On the contrary, the selected macro-economic variables; inflation, GDP growth, interest spread and market concentration were found not to be significant. However, the inclusion of the selected macro-economic indicators improved the logistic regression model classification accuracy with a reduction in type II error though type I error remained the same. In addition, CAMEL and CAMELS achieved the same performance category rating as banks classified as sound fell under the same performance category likewise to those classified as unsound. This can be attributed to the range within a performance category of 0.5 and another 0.1 between performance categories. However, CAMELS performed better in terms of producing distinct ratings hence ranked higher than CAMEL and Z-score index. The study suggested that bank managers focus on ensuring that their banks are well capitalized, minimize nonperforming loans, quality management and adequate liquidity to achieve bank soundness. Similarly, investors and depositors should assess banks based on these significant factors when making their investment and banking decisions. In addition, the CBK should consider implementing CAMELS model for bank financial assessment.
Submitted in partial fulfilment of the requirements for the degree of Master of Commerce at Strathmore University
Keywords: Micro; Macro; Financial soundness assessment; Commercial Banks of Kenya